Is mediation a process of ‘law’? A Hart-Ian perspective - Wong, Jing Zhi (Penerbit Universiti Kebangsaan Malaysia, 2021)
Mediation, as a form of dispute resolution, is widely practiced. Nations across the world recognize it as an increasingly appropriate form of dispute resolution. But the existential question remains. Can we rightly ascribe the word ‘law’ to the processes of mediation? This article makes one qualified proposition. Mediation is an extra-legal process, unless it is used to realize the law (and justice). This is for two reasons. First, mediation’s processes and mediated outcomes do not in themselves cause judges’ obeisance and adherence. Mediated settlements must rely on the law of contract for its validity and efficacy. Second, even if mediation is legislated to form part of our law, it is extra-legal. It does not comport with the minimum content of natural law in that it does not guarantee the realization of the law and access to justice. If we are to regard mediation as law, mediation must be used to realize the law and guarantee access to justice.